EU retail roaming regulation triggers competition mechanisms of wholesale roaming markets that make wholesale prices competitive - Philippe Deniau; Laure Jaunaux; Marc Lebourges (International Telecommunications Society (ITS), 2016)
The European Commission (EC) draft Regulation (2016)2 on wholesale roaming market proposes a massive decrease of the regulated roaming wholesale price caps for data with a drop from exteuro5ct/MB to exteuro0.85 ct/MB to enable the abolition of retail roaming surcharges in Europe by 15 June 2017. However, according to both the “TSM” Regulation text (2015/2120 25th November 2015) itself which imposes the implementation of Roaming Like At Home (RLAH) in Europe and to the decision of the European Court of Justice upholding the first European roaming regulation (ECJ C-58/08 8 June 2010), a wholesale roaming regulation can be justified in parallel of retail regulation only in case of market failure in the wholesale market and in order to prevent the existence of competitive distortions between mobile operators on the internal market. Therefore, wholesale roaming markets regulation should only address identified competitiveness issues. This paper deals with the question of the competitiveness of the wholesale roaming market regarding two angles: the existence of competitive mechanisms and incentives in wholesale roaming markets and the average level of wholesale roaming market prices in comparison with the corresponding level of full production costs. It shows that wholesale roaming markets exhibit competition mechanisms and incentives triggered by roaming volume growth resulting from the perspective of RLAH retail regulation. It also shows that in 2015, the average level of wholesale roaming market prices in Europe is equivalent to the average level of wholesale roaming production costs. Therefore the wholesale roaming market is competitive. Strong regulatory intervention such as large decrease of wholesale roaming caps is neither justified nor proportionate, generates serious risk of distortion of visited markets and jeopardises investments in mobile networks.
Keywords: 330